2015
DOI: 10.1038/srep09742
|View full text |Cite|
|
Sign up to set email alerts
|

Unraveling novel TF-miRNA regulatory crosstalk in metastasis of Soft Tissue Sarcoma

Abstract: Cancer metastasis is a disease of extreme clinical relevance, as it is responsible for more than 90% of cancer-associated mortality. The molecular mechanism and critical regulators involved in this complex multi-stage process of metastasis is poorly deciphered in soft tissue sarcomas (STS), a heterogeneous group of rare tumors with high metastatic potential. Therefore, we aimed at identifying miRNA and transcription factor (TF) regulatory networks and paths in STS metastasis. We integrated mRNA and miRNA expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…This confirmed miR-429 targets KIAA0101 and thereby regulated the processes of metastasis. KIAA0101 as a direct target of miR-429 was further validated by using a reporter system which revealed that miR-429 specifically down- Additionally, co-expression with other STS metastasis markers which are usually upregulated during metastasis of STS like MKI67 and TYMS (a marker hypothesized by our previous study to be involved in STS metastasis), showed significant positive correlation with KIAA0101 [31,32]. Thus, KIAA0101 overexpression correlating with MKI67 is in accordance with studies that have previously shown it to be associated with survival and tumor grade of other cancers like adrenal cancer [29], gastric cancer [20], etc.…”
Section: Discussionmentioning
confidence: 94%
“…This confirmed miR-429 targets KIAA0101 and thereby regulated the processes of metastasis. KIAA0101 as a direct target of miR-429 was further validated by using a reporter system which revealed that miR-429 specifically down- Additionally, co-expression with other STS metastasis markers which are usually upregulated during metastasis of STS like MKI67 and TYMS (a marker hypothesized by our previous study to be involved in STS metastasis), showed significant positive correlation with KIAA0101 [31,32]. Thus, KIAA0101 overexpression correlating with MKI67 is in accordance with studies that have previously shown it to be associated with survival and tumor grade of other cancers like adrenal cancer [29], gastric cancer [20], etc.…”
Section: Discussionmentioning
confidence: 94%
“…All of these pathways ended in a p53/has‐miR‐215/thymidine synthetase sequence . Myc appears to be a key upstream factor in these pathways being influenced by either AP‐2 or BMP2/has‐miR24 sequence .…”
Section: Noncoding Rnas In Sarcomasmentioning
confidence: 99%
“…miR‐182 also appears to be involved in metastatic disease in sarcomas; its expression increases the pulmonary metastatic tendency of sarcomas in mice, which is inhibited by Kruppel‐like factor 3 . In the analysis of sarcoma metastasis, 12 statistically significant pathways involving transcription factors and miRNAs were identified . All of these pathways ended in a p53/has‐miR‐215/thymidine synthetase sequence .…”
Section: Noncoding Rnas In Sarcomasmentioning
confidence: 99%
See 1 more Smart Citation
“…This revolutionary unearthing of human transcriptome tended to shift the paradigm that the proteins (encoded by messenger RNAs) control the fate of the cells. The new classes of rncRNAs discovered from the high-throughput RNA-Seq studies demonstrated their potential regulatory roles in diverse cellular processes such as cellular differentiation, development, homeostasis and many more biological processes [3][4][5][6][7]. These rncRNAs include microRNA (miRNA), small interfering RNA (siRNA), piwi-interacting RNA (piRNA), long non-coding RNA (lncRNA), circular RNA (circRNA) and much more.…”
Section: Editorialmentioning
confidence: 99%